Serafina and the black cloak - Beatty, Robert, 1963- (Disney/Hyperion, 2016)
At the Biltmore Estate in 1899 North Carolina, no one knows that Serafina and her father, the estate's maintenance man, live secretly in the mansion's basement. But when children at the estate begin disappearing, Serafina knows that a strange man in a black cloak is responsible. Serafina risks everything to team up with Braeden Vanderbilt, the nephew of Biltmore's owners, to expose the man's true identity. In the process, Serafina finds a legacy of magic bound to her own identity and past.